Maize and bean cultivars in monoculture and in two intercropping systems - Ramalho, Magno Antonio P.; Silva, Arnaldo F. da; Aidar, Homero (Pesquisa Agropecuaria Brasileira, 2014)
Three cultivars of maize (Zea mays L.), Cargill 111, Ag 301 and Ag 351 and nine varieties of beans (Phaseolus vulgaris L.), Carioca, Rio Tibagi, Rico-23, Diacol Calima, Goiano Precoce, CNF 010, Venezuela 350, IPA 7419 and Rosinha G-2 were evaluated in two simultaneous planting intercropping systems and as a monoculture. One system consisted of maize and beans planted alternately in the same row. The other system consisted of beans planted between rows of maize. This experiment was conducted at the Centro Nacional de Pesquisa de Milho e Sorgo of EM8RAPA at Sete Lagoas, Minas Gerais, Brazil, during the agricultural year 1981/82. Independently of the bean or maize variety or of the cropping system, a decrease in bean productivity of about 58% was observed in the intercropping compared to the monoculture system. The correlation coefficient of the average growth between the intercropping and monoculture systems was low (r = 0.4), suggesting a possible interaction between bean varieties and the systems. No significant interactions were observed between bean and maize varieties or between maize varieties and cropping system.